2022
DOI: 10.3389/fonc.2022.861638
|View full text |Cite
|
Sign up to set email alerts
|

18F-FDG PET Radiomics as Predictor of Treatment Response in Oesophageal Cancer: A Systematic Review and Meta-Analysis

Abstract: The best treatment strategy for oesophageal cancer patients achieving a complete clinical response after neoadjuvant chemoradiation is a burning topic. The available diagnostic tools, such as 18F-FDG PET/CT performed routinely, cannot accurately evaluate the presence or absence of the residual tumour. The emerging field of radiomics may encounter the critical challenge of personalised treatment. Radiomics is based on medical image analysis, executed by extracting information from many image features; it has be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 37 publications
(110 reference statements)
0
8
0
Order By: Relevance
“…3 ). The meta-analyses in 6 systematic reviews were excluded due to unavailable data [ 34 , 42 , 43 , 48 , 60 , 64 ]. Up to 47 meta-analyses reached a stringent p -value of less than 10 −6 , and 6 meta-analyses presented p -values < 10 −3 .…”
Section: Resultsmentioning
confidence: 99%
“…3 ). The meta-analyses in 6 systematic reviews were excluded due to unavailable data [ 34 , 42 , 43 , 48 , 60 , 64 ]. Up to 47 meta-analyses reached a stringent p -value of less than 10 −6 , and 6 meta-analyses presented p -values < 10 −3 .…”
Section: Resultsmentioning
confidence: 99%
“…In addition, Deantonio et al . 13 included five studies and revealed the potential of 18F-FDG PET-based radiomics to predict pCR in EC NCRT. In comparison, the performance of radiomics using different imaging modalities, including PET, CECT, and MRI, were also described in our sub-analysis, all of which showed great potential in patient stratification with favorable sensitivity and specificity.…”
Section: Discussionmentioning
confidence: 99%
“…Although radiomic analysis seems promising for the management of EC patients by predicting pathological response after NCRT 13 , 14 , there is still a lack of comprehensive assessment of the methodological robustness and quality of EC radiomic studies in CCRT management before their clinical translation. In addition, there has been no report to fully assess the pooled predictive power and potential clinical value of the current radiomic model regarding EC CCRT.…”
Section: Introductionmentioning
confidence: 99%
“…In the literature, only a few studies are available on PET-CT radiomics and oesophageal cancer. A recent systematic review by Deantonio et al, summarising the impact of 18F-FDG PET-CT-based radiomics in predicting the response to neoadjuvant chemoradiotherapy in oesophageal cancer, identified only five studies where radiomics was used to predict a pCR [ 36 ]. These authors concluded that radiomic models exhibited a good performance in predicting pathological complete responses (pCRs), with a pooled area under the curve (AUC) of 0.82 (95% CI: 0.74–0.9).…”
Section: Discussionmentioning
confidence: 99%